Prostaglandin F2α 7 d prior to initiation of the 7-d CO-synch + CIDR protocol failed to enhance estrus response and pregnancy rates in beef heifers. (14th April 2018) - Oosthuizen, Nicola; Canal, Luara B; Fontes, Pedro L P; Sanford, Carla D; DiLorenzo, Nicolas; Dahlen, Carl R; Seidel, George E; Lamb, G Cliff
Abstract: To determine the effects of administration of 25 mg of PGF2α 7 d prior to the initiation of the 7-d CO-Synch + controlled internal drug release (CIDR ) fixed-time AI (TAI ) protocol, 985 Bos taurus beef heifers were enrolled in a completely randomized design at 9 locations from April to July of 2016. Within location, all heifers were randomly assigned to 1 of 2 treatments: 1) CONTROL ( n = 496); 100 µg injection of GnRH and a CIDR insert for 7 d [day 7], administration of 25 mg of PGF2α at CIDR removal [day 0], followed by a second injection of GnRH and TAI 54 ± 2 h later; or 2) PRESYNCH ( n = 489); same as CONTROL but heifers received an additional injection of 25 mg of PGF2α 7 d prior [day 14] to CIDR insertion. Estrous detection patches were applied to all heifers on day 14 and were evaluated for estrual activity on day 7. Similarly, estrus alert patches were placed on all heifers on day 0 and evaluated for estrual activity at the time of TAI. Pregnancy was diagnosed via transrectal ultrasonography between 35 and 55 d after TAI. The percentage of heifers exhibiting estrus between days 14 and 7 was greater ( P < 0.001) for the PRESYNCH (70.1 ± 2.4%) than the CONTROL (41.1 ± 2.3%) treatment, whereas the percentage of heifers exhibiting estrus between day 0 and TAI was greater ( P < 0.001) for the CONTROL (55.6 ± 2.4%) than the PRESYNCH (39.7 ± 2.5%) treatment. Estrus response rates differed ( P < 0.001) among locations. Pregnancy rates to TAI differed ( P = 0.023) among locations; however, they did not differ ( P = 0.739) between CONTROL and PRESYNCH treatments (45.4 ± 2.5 vs. 43.2 ± 2.5%, respectively). Final breeding season pregnancy rates did not differ ( P = 0.811) between treatments. Therefore, an injection of PGF2α 7 d prior to initiation of the 7-d CO-Synch + CIDR protocol failed to improve pregnancy rates to TAI in replacement beef heifers.